Rare earth : why complex life is uncommon in the universe - Ward, Peter D. (Peter Douglas), 1949-; Brownlee, Donald (New York : Copernicus, 2000)
In this introduction to the emerging field of astrobiology, a distinguished paleontologist and a noted astronomer team up to provide a fascinating synthesis of what's now known about the rise of life on Earth and how it sheds light on possibilities for organic life forms elsewhere in the universe. Illustrations. First book to synthesize discoveries from astronomy & paleontology regarding the advent of life on earth, & the potential for the development of life on other planets.
Why life might be widespread in the universe -- Habitable zones of the universe -- Building a habitable Earth -- Life's first appearance on Earth -- How to build animals -- Snowball Earth -- The enigma of the Cambrian explosion -- Mass extinctions and the Rare Earth hypothesis -- The surprising importance of plate tectonics -- The Moon, Jupiter, and life on Earth -- Testing the Rare Earth hypotheses -- Assessing the odds -- Messengers from the stars.
Includes bibliographical references and index.
Keywords: Life on other planets; Exobiology